Analysis of the relationship between patient’s satisfaction with the quality of nursing Service and Service in nursing care - Emy Sutiyarsih; Maria Magdalena Setyaningsih (Universitas STRADA Indonesia, 2021)
Caring is essential for a nurse, by which a nurse is able to provide comprehensive nursing care. The purpose of this study is to analyse the relationship between the quality of nursing service and service in caring in nursing towards patients’ satisfaction at X hospital. It’s an Analytical category study with quantitative analytical category using cross sectional design. Sample taken in this study consisted of 66 hospitalized patients, which was divided into a group of patients treated with the implemantion of caring in nursing by the nurses who hadn’t received training program and a group treated by the nurses who had received training program. Result indicates there is a correlation between the quality of nursing service and patients’satisfaction. It is essential that nursing’s primary commitment be maintained in order to promote the quality of nursing service and nurses’ awarness of prioritizing caring in nursing during their nursing service.